2020
DOI: 10.3855/jidc.12879
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory test alterations in patients with COVID-19 and non COVID-19 interstitial pneumonia: a preliminary report

Abstract: Introduction: Coronavirus disease 19 (COVID-19) is the greatest pandemic in modern history. Laboratory test alterations have been described in COVID-19 patients, but differences with other pneumonias have been poorly investigated to date, especially in Caucasian populations. The aim of this study was to investigate differences and prognostic potential of routine blood tests in a series of Italian patients with COVID-19 and non-COVID-19 interstitial pneumonia. Methodology: Clinical data and routine labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 25 publications
6
59
2
2
Order By: Relevance
“…Dynamic monitoring of the inflammation process might be better in predicting the prognosis. Moreover, the results of our study were different from those of previous studies [1,29]. One reason was that there were some missing data in the laboratory results.…”
Section: Plos Onecontrasting
confidence: 99%
“…Dynamic monitoring of the inflammation process might be better in predicting the prognosis. Moreover, the results of our study were different from those of previous studies [1,29]. One reason was that there were some missing data in the laboratory results.…”
Section: Plos Onecontrasting
confidence: 99%
“…This, the consequent lack of information regarding the pathophysiology and clinical progress, prevented the establishment and implementation of adequate public health responses. Several studies have described alterations in routine laboratory tests in patients affected by COVID-19, including a decrease in serum albumin concentrations [8][9][10][11]. However, no pooled analyses of the available evidence have been performed to accurately estimate the effect size of such reduction, to investigate its relationship with disease severity and outcomes and to evaluate which parameters may affect the effect size.…”
Section: Discussionmentioning
confidence: 99%
“…There are ongoing efforts to better understand the pathophysiology, presentation and clinical outcomes of the disease, including the identification of biomarkers for diagnosis, risk stratification, disease monitoring and prognosis. Early studies in COVID-19 patients have reported alterations in routine laboratory tests, particularly white blood cell count, neutrophils, lymphocytes, platelets, alanine aminotransferase, aspartate aminotransferase, D-dimer, total bilirubin and creatinine [8][9][10][11]. Reductions in serum albumin concentrations have also been associated with disease severity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical and demographic factors have been shown to be significantly associated with measures of coronavirus disease 2019 (COVID-19) severity, based on clinical and imaging findings and/or the need for aggressive single- and multi-organ support, and mortality [ 1 , 2 ]. The evidence of excessive inflammatory activity in severe COVID-19, captured during the early phases of the pandemic, prompted the investigation of the clinical role of specific biomarkers of inflammatory and immunomodulating pathways, particularly C-reactive protein (CRP), white blood cell count (WBC), neutrophils, lymphocytes, platelets, procalcitonin, ferritin, and serum amyloid A [ [3] , [4] , [5] , [6] ]. Additional research has shown that patients with COVID-19 can also experience structural and functional abnormalities of specific organs and systems, e.g., cardiovascular, hematological, gastrointestinal, and neurological, in addition to the well-known respiratory compromise, characterized by the development of interstitial pneumonia and acute respiratory distress syndrome (ARDS) [ [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%